The socio-economic disadvantages and development perspectives of the poor in Bangladesh agriculture - Rahman, Atiqur (Dhaka, Bangladesh : Bangladesh Institute of Development Studies, 1986)
This paper is prepared under a collaborative study project between the Bangladesh Institute of Development Studies (BIDS), Dhaka, Bangladesh and the Asian and Pacific Development Centre (APDC), Kuala Lumpur, Malaysia."
"This paper is prepared under a collaborative study project between the Bangladesh Institute of Development Studies (BIDS), Dhaka, Bangladesh and the Asian and Pacific Development Centre (APDC), Kuala Lumpur, Malaysia."
Master microform held by: DLC.
Bibliography: p. 84-86.
aia 04/04/2019
Loans
Keywords: Agriculture--Economic aspects; Agriculture Social aspects; Rural development; Bangladesh